Percutaneous Sacroplasty with or without Radiofrequency Ablation for Treatment of Painful Sacral Metastases - Tian, Q.-H.; -Han, K.; Wang, T.; Min, D.-L.; Wu, C.-G. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Percutaneous sacroplasty is a variation of percutaneous vertebroplasty that has gained attention as a therapeutic option for patients with painful sacral insufficiency fractures due to osteoporosis or metastases. Additionally, percutaneous sacroplasty can also be used to treat painful sacral metastases without a pathologic fracture. The purpose of this retrospective study was to compare the efficacy and safety of fluoroscopy-guided percutaneous sacroplasty alone versus percutaneous sacroplasty plus radiofrequency ablation for the treatment of painful sacral metastases.MATERIALS AND METHODS: For this retrospective study, 126 patients (with a total of 162 painful sacral metastases) were enrolled from October 2012 to February 2021 and assigned to receive either percutaneous sacroplasty plus radiofrequency ablation (n = 51, group A) or percutaneous sacroplasty alone (n = 75, group B). Four different approaches were used for percutaneous sacroplasty: transiliac, interpedicular, anterior-oblique, and posterior. The Visual Analog Scale, Oswestry Disability Index, and Karnofsky Performance Scale were used to evaluate outcomes.RESULTS: The Visual Analog Scale, Oswestry Disability Index, and Karnofsky Performance Scale scores showed significant improvement in both groups after treatment (P < .05). The overall pain relief rate was significantly better in group A than in group B (90% versus 76%, P = .032). There were no significant differences in the incidence of polymethylmethacrylate leakage between the 2 groups or among the 4 different approaches (P > .05).CONCLUSIONS: Both percutaneous sacroplasty alone and the combination of percutaneous sacroplasty and radiofrequency ablation are safe and effective for treatment of painful sacral metastases. The combination of percutaneous sacroplasty and radiofrequency ablation appears to be more effective than percutaneous sacroplasty alone.KPSKarnofsky Performance ScaleODIOswestry Disability IndexPMMApolymethylmethacrylatePSPpercutaneous sacroplastyRFAradiofrequency ablationVASVisual Analog Scale